Utilização da fotocatálise solar heterogênea no tratamento de efluentes industriais - Silva , Elson Santos da (2016)
Treatment of textile wastewater and biodiesel industry has a great interest from an environmental point of view, not only by the volume of waste generated, but its composition. The textile industry has the characteristic of generating huge amounts of residues, mainly the ones from yarns and fabrics dyeing operations. The effluent from the biodiesel industry is considered the major polluter of the environment. Conventional treatments of those wastewaters are inefficient for degrading the majority of the compunds. Heterogeneous photocatalysis using titanium dioxide has been arising as a promising alternative for treating this kind of pollutants. In this work, the use of heterogeneous photocatalysis using titanium dioxide in the degradation of biodiesel industry effluent and discoloration of methylene blue dye was studied. In the experiments, the parameters of pH, time of exposure to the sun, catalyst concentration, pollutant concentration, and radiation levels were monitored during 4 hour of experiment period. The methylene blue decoloration results showed significant values removal of 98.67% and 99.39% for the dye concentrations of 50 mg.L-1 and with the catalyst concentration of 0.5 g.L-1. The methylene blue concentration up to 20 mg.L-1 showed 100% color removal. The best results from the degradation of chemical oxygen demand of the biodiesel effluent (74.82% and 42.85%) were obtained at pH 3.0 conditions and concentrations of the catalyst of 0.5 g. L-1 and 0.3 g. L -1 respectively and 45.75% in the conditions of pH 5.0 and the catalyst concentration of 0.7 g.L-1. The results of the biodiesel effluent degradation have been conditioned to the initial chemical oxygen demand and the concentration of the salts in the effluent.